'You can't say, "what about me?" I'm not the one with cancer': information and support needs of relatives. Issue 6 (24th October 2014) - Foster, Claire; Myall, Michelle; Scott, Isobel; Sayers, Mary; Brindle, Lucy; Cotterell, Phil; Addington‐Hall, Julia; Hopkinson, Jane; Payne, Sheila; Robinson, Judith
Abstract Objective The aims of this study were to explore relatives' experiences of talking about cancer within the family and to identify their information and support needs. Method A cross‐sectional in‐depth interview study with relatives and partners (n = 22) of cancer patients recruited through community settings was conducted. A thematic approach was used for analysis. Results Information sharing and communication within families operated within a context of cancer‐related uncertainty. Discussion about cancer was generally viewed as beneficial, but relatives faced dilemmas, which inhibited information exchange. Participants often devised strategies to manage the challenges faced to fulfil their needs for information and support. This was deemed important as talking about cancer allowed relatives to support patients' preferences for care, deal with practical demands and come to terms with difficult issues. Lack of information was perceived to affect the quality of care participants could provide. Conclusion Participants did not always want to know everything about the patient's illness, suggesting the importance of tailoring information to individual needs. Offering a range of different kinds of support directly to relatives may improve patient care and emotional well‐being. Copyright © 2014 John Wiley & Sons, Ltd.